2018
DOI: 10.1371/journal.pone.0204331
|View full text |Cite
|
Sign up to set email alerts
|

The clinical relevance of ABO blood type in 100 patients with acute subdural hematoma

Abstract: ObjectiveThe correlation of depleted blood through midline shift in acute subdural hematoma remains the most reliable clinical predictor to date. On the other hand, patient’s ABO blood type has a profound impact on coagulation and hemostasis. We conducted this study to evaluate the role of patient’s blood type in terms of incidence, clinical course and outcome after acute subdural hematoma bleeding.Methods100 patients with acute subdural hematoma treated between 2010 and 2015 at the author’s institution were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 24 publications
1
13
1
Order By: Relevance
“…Since the ABO blood groups are suspected to be associated with various health conditions 32 , 33 , we analyzed the association between predicted ABO blood groups and self-reported clinical phenotypes in the TWB cohort. We found that blood type O was less likely to be associated with epilepsy, consistent with the findings of a previous study 34 , and that TWB participants with blood type AB had a significantly higher incidence rate of epilepsy compared to type O participants (OR = 1.84, 95% CI ~1.2–2.8).…”
Section: Resultssupporting
confidence: 91%
“…Since the ABO blood groups are suspected to be associated with various health conditions 32 , 33 , we analyzed the association between predicted ABO blood groups and self-reported clinical phenotypes in the TWB cohort. We found that blood type O was less likely to be associated with epilepsy, consistent with the findings of a previous study 34 , and that TWB participants with blood type AB had a significantly higher incidence rate of epilepsy compared to type O participants (OR = 1.84, 95% CI ~1.2–2.8).…”
Section: Resultssupporting
confidence: 91%
“…Although some studies have shown that peripheral vasospasm is related to increase levels of VIII factor, [6,23,24] this evidence may not be necessary transposable to cerebrovascular conditions after aSAH. Furthermore, the amount of bleeding and presumably, a faster clot liquidation [3] in "O" type patients can propitiate an environment within the subarachnoid space in which abnormal high levels of hemoglobin and oxidized heme products can intercept with high affinity free NO [14] and synthetize endogenous eNOS [22] inhibitors, leading to dysregulation of vascular tone and therefore, DCI onset.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study investigated the influence of ABO blood group on outcome subdural hematoma. 7 Patients with blood type O that were found to have a decreased midline shift, a lower postoperative epileptic seizure incidence. In terms of rebleeding rate no significant difference between O and non-O patients were found (OR 0.65; 95% CI [0.23-1.82]; P=0.291) and morbidity outcome, expressed through the GOS (Glasgow Outcome Scale) at 3 months, showed no significant difference between O and non-O patients either (P=0.504 mean GOS 3).…”
Section: Discussionmentioning
confidence: 99%